STRATEGY OF ILLITERACY ELIMINATION PROGRAM IN IMPROVING LITERACY SKILLS OF INMATES AT CLASS IIB PRABUMULIH PRISON - Hartawan, Aldi Satrio; Rohayati, Ade Cici (Universitas Nusa Cendana, 2025)
This study aims to identify strategies for the illiteracy eradication program to improve the literacy skills of inmates at the Class IIB Prabumulih Detention Center. The background of this research is the high illiteracy rate in Indonesia, particularly among inmates, which poses challenges in their rehabilitation and social reintegration efforts. The research method used is qualitative with a descriptive approach, involving direct observation, interviews, and documentation. The results show that the strategies implemented in this program include mapping the literacy needs of inmates, designing a curriculum based on their needs, utilizing interactive learning methods, and receiving support from competent educators. The challenges faced include low motivation among inmates and limited resources and facilities. However, the program has proven effective in enhancing the reading, writing, and arithmetic skills of the inmates. In conclusion, the illiteracy eradication program at Class IIB Prabumulih Detention Center has a positive contribution to inmate rehabilitation efforts, but improvements in resources and external collaboration are needed to overcome existing challenges. Keywords: Illiteracy Eradication; Literacy; Inmates; Rehabilitation; Class IIB Prabumulih Detention Center